Sustainability Reporting in Third Sector Organizations: A Systematic Literature Review (European journal of volunteering and community-based projects, 2025)
Purpose: This study aims to analyze the existing literature on Sustainability Reporting (SR) in Third Sector Organizations (TSOs), assessing its impact on transparency, accountability, and stakeholder engagement. Given the increasing relevance of sustainability disclosures across various sectors, this research identifies key trends, challenges and opportunities associated with SR adoption in TSOs. Design/methodology/approach: This study employs a Systematic Literature Review (SLR) methodology, following the PRISMA framework and integrating bibliometric analysis. Articles were retrieved from Scopus and Web of Science, applying predefined inclusion and exclusion criteria. The selected literature was analyzed using Bibliometrix and VOSviewer software.                      Findings: The results indicate that SR enhances the reputation, the transparency, the legitimacy, and stakeholder engagement of TSOs. Despite its advantages, several barriers hinder its adoption, including lack of clear regulatory frameworks, absence of uniform regulatory standards, and difficulties in measuring social and environmental performance.    Research implications: The findings provide valuable insights both from a theoretical perspective—by identifying research gaps and offering a solid foundation for scholars to conduct future investigations on the topic—and from a practical standpoint, serving as a useful reference for TSO managers and policymakers.Originality/Value: This study fills a gap in the literature by providing a comprehensive synthesis of SR practices in TSOs. It extends prior research by combining systematic review techniques with bibliometric analysis, offering a structured perspective on the challenges and opportunities associated with sustainability disclosures in the non-profit sector.
Keywords: sustainability; sustainability reporting; third sector organizations; non-profit sector; systematic literature review; sustainable development goals; non-financial disclosure